PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA KELAS VI PADA MATA PELAJARAN IPAS UPT SDN PANAIKANG II - Hasriani; Nurlina; Nasharuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The results of the 2022 PISA test indicate that the critical thinking skills of elementary school students remain relatively low. This study aims to analyze the effect of Project-Based Learning (PjBL) on students’ critical thinking skills in Science and Social Studies lessons in the sixth grade at UPT SDN Panaikang II. The method used was a quasi-experiment with a nonequivalent group design involving 55 students, consisting of 27 students in the control group and 28 students in the experimental group. The analysis results showed that the mean score for critical thinking skills in the control class increased from 37.50 on the pretest to 47.53 on the posttest, while in the experimental class, there was a more significant increase from 23.66 to 62.05. Furthermore, based on the average scores of all indicators, the control class improved from 34% to 45%, while the experimental class improved more significantly from 20% to 60%. The results of the independent samples t-test showed a significance value (Sig. 2-tailed) of 0.031, indicating a significant difference between the control class and the experimental class, which suggests that the implementation of the PjBL learning model has a significant effect on improving students’ critical thinking skills.